Origin of Opal-CT in Lower Eocene Tallahatta Formation, Mississippi, USA and Pleistocene Barind Clay Formation in Bangladesh: A Comparative Study: Origin of Opal-CT - Kabir, Sohail (Biological Sciences - PJSIR, 2008)
Opal-CT mineral in the lower Eocene Tallahatta formation in Mississippi, USA and the Pleistocene Barind clay formation in Bangladesh is of volcanogenic origin. X-ray diffraction patterns of claystones in the former indicated more ordered condition of the older sediments than those of the latter, which may be due to higher burial temperatures and longer time interval for transformation from volcanic ash to opal-CT of the former. Glass shards, present in the latter sediments, were not identified in the former, which may be due to transformation of glass shards of volcanic ash to opal-CT over the time.